(untitled) (International journal of artificial intelligence, 2025)
The main part (about 50%) of the 4304.32 thousand hectares of irrigated land of our republic is saline soils to varying degrees, which reduces the overall productivity of agricultural crops in irrigated areas. This article provides detailed information on the irrigated soils of the Olot district and their properties. In addition, measures to improve soil fertility are presented.